2014
DOI: 10.1111/ped.12329
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of electrocardiographic parameters for early diagnosis of autonomic dysfunction in children and adolescents with type‐1 diabetes mellitus

Abstract: Cardiac autonomic function disorder, which is one of the most important causes of morbidity and mortality, may emerge in the course of type 1 diabetes mellitus. It can be diagnosed on ECG even when the patients are asymptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…7,41,42 In the present study, we found a positive correlation between therapeutic response and QTcd value, thus supporting this possible mechanism for physical treatment.…”
Section: Discussionsupporting
confidence: 79%
“…7,41,42 In the present study, we found a positive correlation between therapeutic response and QTcd value, thus supporting this possible mechanism for physical treatment.…”
Section: Discussionsupporting
confidence: 79%
“…Further investigations are necessary to elucidate this finding and its relevance in DCM. In children with T1DM, P wave dispersion was higher compared to controls [44].…”
Section: Plos Onementioning
confidence: 69%
“…Cardiac autonomic neuropathy (CAN) consists of sympathetic and parasympathetic dysfunction and it is known to lead to sudden death in adults. QTc interval has been used to demonstrate CAN in adults rather than prolonged ventricular depolarization and repolarization (12). Marthur et al (13) conducted a study with 50 asymptomatic adult patients with diabetes in 2006 and found findings of CAN in 19 patients; QTc prolongation was found in 15 of these patients.…”
Section: Discussionmentioning
confidence: 99%